Inequality and diversity in sport - Developments and perspectives - Markus Lamprecht; Siegfried Nagel (Bern Open Publishing, 2023)
Despite the steady increase in the number of people active in sport over the past decades, certain population groups are still underrepresented in sport and especially in sport clubs, e.g. people with a low level of education and income, with a migration background or disabilities. In view of the diverse functions attributed to sport involvement, such as health promotion, transmission of norms and values, and social integration, analyses of social inequalities with regard to sport participation are of particular relevance. The symposium organized by the Research Committee for the Sociology of Sport aims, on the one hand, to highlight current developments and relevant factors with regard to the participation of different population groups in sport and, on the other hand, to present possibilities in the sense of diversity management of how sport organizations can facilitate access to sport. This will provide a knowledge base on the question of how to reduce barriers to access in sport and ensure greater equality. The first two presentations highlight developments with regard to social differences in the sport behavior of the Swiss population. Bürgi and Lamprecht analyze the effects of the Covid 19 pandemic and Klostermann et al. examine historical changes in sport behavior. The two other contributions look at specific target groups and the importance of structural conditions. Klenk et al. focus on the social participation of children with cognitive impairment in inclusive school sport. Buser and Nagel show how inclusive measures for people with a migration background are structurally anchored in soccer clubs.